Focused Fluid Flow Along the Nootka Fault Zone and Continental Slope, Explorer‐Juan de Fuca Plate Boundary. (20th August 2020) - Riedel, M.; Rohr, K. M. M.; Spence, G. D.; Kelley, D.; Delaney, J.; Lapham, L.; Pohlman, J. W.; Hyndman, R. D.; Willoughby, E. C.
Abstract: Geophysical and geochemical data indicate there is abundant fluid expulsion in the Nootka fault zone (NFZ) between the Juan de Fuca and Explorer plates and the Nootka continental slope. Here we combine observations from >20 years of investigations to demonstrate the nature of fluid‐flow along the NFZ, which is the seismically most active region off Vancouver Island. Seismicity reaching down to the upper mantle is linked to near‐seafloor manifestation of fluid flow through a network of faults. Along the two main fault traces, seismic reflection data imaged bright spots 100–300 m below seafloor that lie above changes in basement topography. The bright spots are conformable to sediment layering, show opposite‐to‐seafloor reflection polarity, and are associated with frequency reduction and velocity push‐down indicating the presence of gas in the sediments. Two seafloor mounds ~15 km seaward of the Nootka slope are underlain by deep, nonconformable high‐amplitude reflective zones. Measurements in the water column above one mound revealed a plume of warm water, and bottom‐video observations imaged hydrothermal vent system biota. Pore fluids from a core at this mound contain predominately microbial methane (C1 ) with a high proportion of ethane (C2 ) yielding C1 /C2 ratios <500 indicating a possible slight contribution from a deep source. We infer the reflective zones beneath the two mounds are basaltic intrusions that create hydrothermal circulation within the overlying sediments. Across the Nootka continental slope, gas hydrate‐related bottom‐simulating reflectors are widespread and occur at depths indicating heat flow values of 80–90 mW/m 2 . Key Points: Fluid flow is focused along Nootka Fault traces resulting in shallow bright spots Two seafloor mounds are the result of basaltic intrusions in the Nootka fault zone Gas hydrates occur at the Nootka Slope and are imaged seismically as bottom‐simulating reflectors suggesting a regional heat flow of ~80 mW/m 2 along the slope